2000
DOI: 10.1080/026404100446739
|View full text |Cite
|
Sign up to set email alerts
|

Physiological requirements of cricket

Abstract: Despite its long history and global appeal, relatively little is known about the physiological and other requirements of cricket. It has been suggested that the physiological demands of cricket are relatively mild, except in fast bowlers during prolonged bowling spells in warm conditions. However, the physiological demands of cricket may be underestimated because of the intermittent nature of the activity and the generally inadequate understanding of the physiological demands of intermittent activity. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 20 publications
3
121
1
Order By: Relevance
“…It was 38 years later when it was reported that during an ODI game, batsmen had sweat rates, heart rates and rectal temperatures of up to 6 L.h -1 , 120 beats.min -1 and 38.5 o C respectively. [6] This led to the conclusion that cricket was more physically demanding than previously thought, a statement that was further validated by Noakes and Durandt [3] in 2000. Since then other studies have been conducted in these authors' laboratory.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…It was 38 years later when it was reported that during an ODI game, batsmen had sweat rates, heart rates and rectal temperatures of up to 6 L.h -1 , 120 beats.min -1 and 38.5 o C respectively. [6] This led to the conclusion that cricket was more physically demanding than previously thought, a statement that was further validated by Noakes and Durandt [3] in 2000. Since then other studies have been conducted in these authors' laboratory.…”
mentioning
confidence: 96%
“…Furthermore, a batsman scoring a century runs 40 singles, eight twos, three threes and hits an average of seven fours and two sixes after spending approximately 136 minutes at the crease. [2,3] Thus it is evident that both the physical and psychological load placed on the players is increasing. However, these demands have not received much attention, most likely because the game is intermittent in nature and therefore difficult to study.…”
mentioning
confidence: 99%
“…[1,19,27] e multi-stage tness test is recommended to test aerobic power as it is inexpensive, easy to administer and applicable to many team sports with respect to the stop, start and change-of-direction movement patterns. [24] One study [14] showed that cricketers had a higher shuttle run number when compared with rugby union players, with a VO 2max of ~6 0 ml/kg / min. Johnstone and Ford [21] established physical fitness profiles of cricketers grouped into bowlers and batsmen (n=15) using this test.…”
Section: Aerobic and Anaerobic Tnessmentioning
confidence: 99%
“…[14] For example, there is little logic in using only a vertical jump test when research and observation show that elders need to move in all directions and consequently need multi-directional lower-leg strength and power. Correctly assessing the multi-planar movement ability of elders should lead to better training programmes.…”
Section: Lower Bodymentioning
confidence: 99%
See 1 more Smart Citation